Combination Therapy in the Management of Hypertension: Focus on Angiotensin Receptor Blockers Combined With Diuretics - Palatini, Paolo (J Clin Hypertens (Greenwich), 2007)
There is increasing evidence that combination therapy should be emphasized more than it is at present for the initial treatment of hypertensive patients. Recent guidelines acknowledge the value of combination therapy, although some treatment algorithms fail to echo this message. Observations from major clinical trials in the elderly, diabetics, stroke patients, and African Americans all indicate that combination therapy is necessary to control blood pressure in the majority of these patients. Several combination therapies such as an angiotensin II receptor blocker and a diuretic, an angiotensin‐converting enzyme inhibitor with a diuretic, a β blocker with a diuretic, or an angiotensin‐converting enzyme inhibitor with a calcium antagonist have been shown to be effective in patients who do not respond to monotherapy. The current review focuses on the newest such combination; an angiotensin II receptor blocker and a diuretic may have an added advantage of being well tolerated. Recent studies have shown that angiotensin II receptor blockers, given alone or combined with a diuretic, may prevent some cardiovascular outcomes independent of their blood pressure‐lowering efficacy.